Dental Caries Prevention Strategies, Application of Evidence-Based Medicine. Part 3. Oral Hygiene in Dental Caries Prevention - Z. Broukal; J. Dušková; V. Merglová; R. Koberová-Ivančaková; E. Ryšlavá (Czech Dental Chamber, 2017)
Background: The third part of the literature review presents evidences that have been so far gathered on the significance of oral hygiene, oral hygiene means and techniques in the prevention of dental caries in children, youth and adults. The review describes epidemiologic associations of oral hygiene and dental caries, demands on oral hygiene in caries prevention, means, techniques a tooth brushing regimes.The quality of evidence on basic parameters of oral hygiene means and techniques of their employment and the weight of clinical recommendations is summarized. The cited data on their effect are taken mainly from meta-analytic studies and reports from Cochrane database systematic reviews and from longitudinal randomized controlled trials. Mentioned below are the basic documents of national and international professional organizations and expert panels that consistently formulate appropriate recommendations and procedures for oral hygiene in caries prevention in the principles of evidence-based medicine. Conclusion: Current guidelines strictly accentuate the personalized approach to oral hygiene means, techniques and regimes with regard to an individual's oral health status and a risk rate of its impairment.